ТЕОРЕТИЧНІ ОСНОВИ ПІДГОТОВКИ СТУДЕНТІВ ДО ТВОРЧОЇ ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ В УМОВАХ ПЕДАГОГІЧНОГО УНІВЕРСИТЕТУ ЗАСОБАМИ ІНОЗЕМНОЇ МОВИ (Педагогіка вищої та середньої школи, 2022)
This article deals with the question of formation of student creative abilities. The author shows the specific conditions to for students’ creative abilities at schools of higher learning.